Inovasi Instrumen Penilaian Proyek Berbasis Teori Transaction Terhadap Mahārah Kitābah Pada Buku Ajar Bahasa Arab - Busyro Husaini; Aulia Ulhaq; Safitri Mugindari (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The study explores innovation in assessing Arabic writing skills (maharah kitabah) through a project-based approach grounded in Transaction Theory. It critiques the 2020 Indonesian Ministry of Religious Affairs’ Arabic textbook for grade XI, highlighting its limited exercises that nurture students’ written self-expression. Employing library research, the study reviews literature relevant to writing assessment and develops a theoretical model for evaluating writing competence. Findings reveal that project-based assessment can be structured into three core stages—planning, implementation, and reporting—supported by a comprehensive rubric. Assessment aspects include sentence structure, word formation, grammar usage (nahwu–sharaf), writing style, content quality, creativity, vocabulary accuracy, and use of authentic Arabic expressions. This model allows for both formative and summative evaluation, ensuring objectivity and clarity. It not only measures technical proficiency but also provides space for students to express aesthetic, cultural, and philosophical dimensions through writing. Ultimately, the proposed assessment model aims to enhance the quality of Arabic writing instruction and overcome the limitations found in the current textbook evaluations.